Elasto-plastic shear behavior of reinforced honeycomb and auxetic reentrant lattices - Vitor Carneiro; José Meireles (Instituto Politécnico de Viseu, 2018)
Introduction: Auxetic materials possess a negative Poisson's ratio. Even though, the existence of isotropic auxetics is theoretically possible, they seem to be absent in natural states thus, there has been an effort to produce artificial auxetics mostly by the design of inverted (reentrant) honeycombs. Objetives: This study explores a novel Reinforced Honeycomb Lattices and Auxetic Reentrant lattices to enhance structural elasto-plastic behaviour in shear deformation. Methods: Finite element analysis (FEA) is used to simulate shear loading in Reinforced Honeycomb and Auxetic Reentrant lattices, while the imposed stress and strains are monitored. Results: Auxetic transformation promotes an increase in shear modulus, however, it generates plastic strains at lower values of shear deformation. However, the closing effect of auxetic materials, tends to reduce the plastic affected area. Conclusions: In this study, a novel generation of Reinforced Honeycomb and Auxetic Reentrant Lattices are presented. Even though, the auxetic transformation generates plastic strain for lower shear deformation regimes, it is able to reduce the areas affected by plasticity and elevate shear stiffness.